IBM z/OS V1R13 Communications Server TCP/IP Implementation Volume 1 Base Functions, Connectivity, and Routing - Ebbers, Mike; Ayyar, Rama; Ferreira, Octavio L.; Ojima, Yohko; Cesar de Oliveira, Gilson; Riches, Mike; Xavier, Maulide (IBM Redbooks, 2012)
For more than 40 years, IBM® mainframes have supported an extraordinary portion of the world's computing work, providing centralized corporate databases and mission-critical enterprise-wide applications. The IBM System z®, the latest generation of the IBM distinguished family of mainframe systems, has come a long way from its IBM System/360 heritage. Likewise, its IBM z/OS® operating system is far superior to its predecessors in providing, among many other capabilities, world-class and state-of-the-art support for the TCP/IP Internet protocol suite. TCP/IP is a large and evolving collection of communication protocols managed by the Internet Engineering Task Force (IETF), an open, volunteer organization. Because of its openness, the TCP/IP protocol suite has become the foundation for the set of technologies that form the basis of the Internet. The convergence of IBM mainframe capabilities with Internet technology, connectivity, and standards (particularly TCP/IP) is dramatically changing the face of information technology and driving requirements for even more secure, scalable, and highly available mainframe TCP/IP implementations. The z/OS Communications Server TCP/IP Implementation series provides understandable, step-by-step guidance about how to enable the most commonly used and important functions of z/OS Communications Server TCP/IP. This IBM Redbooks® publication is for people who install and support z/OS Communications Server. It introduces z/OS Communications Server TCP/IP, discusses the system resolver, showing implementation of global and local settings for single and multi-stack environments. It presents implementation scenarios for TCP/IP base functions, connectivity, routing, virtual MAC support, and sysplex subplexing.
Title from content provider
Keywords: z/OS; Operating systems (Computers); Client/server computing; TCP/IP (Computer network protocol); Information storage and retrieval systems; Communications software; Architecture client-serveur (Informatique); Logiciels de communication; Systèmes d'exploitation (Ordinateurs); TCP/IP (Protocole de réseaux d'ordinateurs); Systèmes d'information; operating systems